Why has India's counterinsurgency strategy been more successful than Pakistan's and what should Pakistan do to enhance or improve its strategy? a comparative analysis of Indian and Pakistani efforts to counter insurgencies. - Harshita Kohli. (2013)
Pakistan has been a sanctuary over the years for numerous terrorist organizations but with militant groups like the Taliban, Al Qaeda, Lashkar-e-Toiba and Tehrik-iTaliban